The Benefits of Using Social Media and the Impact of not filtering the Information - Mohd Helmi Masor@Mansor; Nor Zaina Zaharah Mohamad Ariff; Norliya Ahmad Kassim; Mohd Shamsul Mohd Shoid; Che Zainab Abdullah; Kasmarini Baharuddin; Noreen Natasha Azmee; Razman Radzi (Universiti Sains Islam Malaysia, 2024)
This preliminary study aims to examine the perceptions of students on the benefits of using social media and the impact of not filtering the information. A set of questionnaire has been distributed to 50 students from the Faculty of Information Management, Universiti Teknologi MARA (UiTM), Puncak Perdana, Shah Alam Malaysia. Thirty-six (36) or 72 per cent of the questionnaires were returned and were used for analysis. Results show that students have positive perceptions on the benefits of using social media (mean = 4.01). They agree that using social media will increase connectivity and encourage information-sharing among friends. The findings also show that students agree on the impact of not filtering information (mean = 4.00), which may cause confidential information to be used for blackmailing purposes. The outcome of this study is important as it reflects on students’ awareness on the benefits of social media and the impact of unfiltered information.